Small Bowel Pseudomelanosis Associated with Oral Iron Therapy - Kim, Seung Young (The Korean Academy of Medical Sciences, 2013)
An accumulation of pigment deposits on mucosa, called melanosis or pseudomelanosis, of the small bowel is observed infrequently during endoscopic examination. We describe 6 cases of small bowel pseudomelanosis; the possible etiology of which was chronic iron intake. We observed numerous brown spots in duodenum, jejunum, and terminal ileum during upper and lower endoscopy. Interestingly, all patients have been taking oral iron for several years. Histology showed pigment depositions within macrophages of the lamina propria and a positive Prussian blue stain indicating hemosiderin deposition. Herein, we demonstrate that long term iron therapy may result in pseudomelanosis of small bowel, such as duodenum, jejunum, and ileum.